Artikel Review: Kandungan Senyawa Aktif Tanaman Untuk Kesehatan Kulit - Gunarti, Neni; Yuniarsih, Nia; Toni. S, Rifqi Maulana; Khoerunnisa, Rita; Allahuddin, Allahuddin; Anggraeni, Fera; Ruhdiana, Tita (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Abstract: Background: Skin is the outermost organ of the body that coats the human body that needs to be treated to prevent skin damage from free radicals or infection. The way to maintain and care for the skin is using synthetic compounds that can help maintain healthy skin. Another alternative in skin care is to use plants that have active compounds that are beneficial for skin health and have relatively low side effects compared to synthetic chemicals. Objective: This study aimed to determine the active compounds of plants that can improve skin health. Method: Article review using Google Schoolar database with keywords related to the research topic, namely